2020
DOI: 10.1021/acs.jpclett.0c00020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Magnetic Properties of the Largest Single-Molecule Magnets

Abstract: The giant {Mn 70 } and {Mn 84 } wheels are the largest nuclearity single-molecule magnets synthesized to date and understanding their magnetic properties poses a challenge to theory. Starting from first principles calculations, we explore the magnetic properties and excitations in these wheels using effective spin Hamiltonians. We find that the unusual geometry of the superexchange pathways leads to weakly coupled {Mn 7 } subunits carrying an effective S = 2 spin. The spectrum exhibits a hierarchy of energy sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…As discussed in [17], using only the 3J model (J 1 , J 2 , J 3 in Fig. 2) results in a large ground-state degeneracy in a classical Ising or Potts model, with ground-state spins ranging from S = 0 to S = 24.…”
Section: A Exchange Interaction Constantsmentioning
confidence: 87%
See 1 more Smart Citation
“…As discussed in [17], using only the 3J model (J 1 , J 2 , J 3 in Fig. 2) results in a large ground-state degeneracy in a classical Ising or Potts model, with ground-state spins ranging from S = 0 to S = 24.…”
Section: A Exchange Interaction Constantsmentioning
confidence: 87%
“…In previous work, we showed that using first-principles density functional theory (DFT) derived exchange couplings, together with a coarse-grained theoretical treatment of the spins, it was possible to uncover the origin of the small but non-zero ground-state spin. In particular, the small long-range exchange couplings renormalize into coarse-grained quadratic spin-spin effective couplings between clusters of spins, generating the small non-zero ground-state spin [17].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have argued that the low-spin plateau found for the FM-AFM sawtooth chain is a finite-size effect related to the competition of the incommensurate infinite-system spiral with finite-system spirals of wavelength λ = L, L/2. An intriguing question is whether the same physics underlies the Mn wheels (as well as related magnetic molecules [12]), which are finite systems of 70-84 magnetic centres [13][14][15] and which also exhibit a lowspin ground state stemming from from mixed FM-AFM exchange couplings [15]. In particular, one may wonder whether or not the low-spin state in these systems is also connected to quantum spin spirals with wavelengths spanning across the whole molecule.…”
Section: Discussionmentioning
confidence: 99%
“…That value produces the correct Mn moment in such systems. 55,56 The external electric field is modeled by a saw-tooth potential. 57 The energy barrier for electron transfer from one Mn to another was calculated using the NEB method 41,42,43 as implemented in VASP.…”
Section: Computational Approachmentioning
confidence: 99%